Technostress dan Kesejahteraan Psikologis Pada Mahasiswa Asal Daerah 3T - Shevanya Christiano Semen Tulak; Arthur Huwae (Journal of Psychology and Instruction, 2025)
Indonesia has 62 underdeveloped, outermost, and disadvantaged (3T) regions, which are located far from urban areas and are scattered throughout the country. This situation forces students to migrate, as migrant students are defined as those who continue their education in different regions due to the uneven distribution of higher education. However, the current reality in Indonesia shows an academic gap experienced by students from 3T areas in facing the challenges of technology use in higher education. This condition can lead to technology-based stress, which subsequently affects their psychological well-being. Therefore, this study aims to examine the relationship between technostress and psychological well-being among students from 3T regions. This research employs a quantitative method with a correlational design. A total of 411 students from 3T areas participated, selected using accidental sampling techniques. The research measurement utilized the technostress scale and the Ryff Scale of Psychological Well-Being (SPWB). The results indicate a negative relationship between technostress and psychological well-being among students from 3T regions (r = -0.467, sig = 0.000, p < 0.01). This means that when there is an increase or decrease in technostress experienced by students from 3T.